Nitric oxide-mediated regulation of mitochondrial protective autophagy for enhanced chemodynamic therapy based on mesoporous Mo-doped Cu9S5 nanozymes. (1st October 2022) - Zhou, Zhaoru; Gao, Zhimin; Chen, Wei; Wang, Xiaozhao; Chen, Zhankun; Zheng, Zhaocong; Chen, Qianyi; Tan, Meiling; Liu, Donglian; Zhang, Yaru; Hou, Zhiyao
Abstract: The depletion of reactive oxygen species (ROS) by glutathione (GSH) and oxidative stress induced protective autophagy severely impaired the therapeutic effect of chemodynamic therapy (CDT). Therefore, how to construct a CDT treatment nanosystem with high yield and full utilization of ROS in tumor site is the main issue of CDT. Herein, a multifunctional cascade bioreactor based on mesoporous Mo-doped Cu9 S5 (m-MCS) nanozymes loaded with L-Arginine (LA), abbreviated as m-MCS@LA, is constructed for realizing enhanced CDT promoted by ultrasound (US) triggered gas therapy. The m-MCS based on the catalytic performance of multivalent metal ions, which were served as nanozymes, exhibit enhanced Fenton-like and glutathione (GSH) peroxidase-like activities in comparison to Cu9 S5 nanoparticles without Mo-doping. Once placed in tumor microenvironment (TME), the existence of redox couples (Cu + /Cu 2+ and Mo 4+ /Mo 6+ ) in m-MCS enabled it to react with hydrogen peroxide (H2 O2 ) to generate ·OH for achieving CDT effect via Fenton-like reaction. Meanwhile, m-MCS could consume overexpressed GSH in tumor microenvironment (TME) to alleviate antioxidant capability for enhancing CDT effect. Moreover, m-MCS with mesoporous structure could be employed as the carrier to load natural nitric oxide (NO) donor LA. US as the excitation source with high tissue penetration can trigger m-MCS@LA to produce NO. As the gas transmitter with physiological functions, NO could play dual roles to kill cancer cells through gas therapy directly, and enhance CDT effect by inhibiting protective autophagy simultaneously. As a result, this US-triggered and NO-mediated synergetic cancer chemodynamic/gas therapy based on m-MCS@LA NPs can effectively eliminate primary tumor and achieved tumor-specific treatment, which provide a possible strategy for developing more effective CDT in future practical applications. Statement of Significance: The depletion of reactive oxygen species (ROS) by glutathione (GSH) and oxidative stress induced protective autophagy severely impaired the therapeutic effect of chemodynamic therapy (CDT). Herein, a multifunctional cascade bioreactor based on mesoporous Mo-doped Cu9 S5 (m-MCS) nanozymes loaded with L-Arginine (m-MCS@LA) is constructed for realizing enhanced CDT promoted by ultrasound (US) triggered gas therapy. The m-MCS with double redox couples presents the enhanced enzyme-like activities to perform cascade reactions for reducing GSH and generating ROS. LA loaded by m-MCS can produce NO triggered by US to inhibit the mitochondria protective autophagy for reactivating mitochondria involved apoptosis pathway. The US-triggered and NO-mediated CDT based on m-MCS@LA can effectively eliminate primary tumor through the high yield and full utilization of ROS. Graphical abstract: Image, graphical abstract